Classification of Aspergillus, Penicillium, Talaromyces and related genera (Eurotiales): An overview of families, genera, subgenera, sections, series and species - Houbraken, J; Kocsubé, S; Visagie, C M; Yilmaz, N; Wang, X-C; Meijer, M; Kraak, B; Hubka, V; Bensch, K; Samson, R A; Frisvad, J C (Studies in mycology, 2020)
The Eurotiales is a relatively large order of Ascomycetes with members frequently having positive and negative impact on human activities. Species within this order gain attention from various research fields such as food, indoor and medical mycology and biotechnology. In this article we give an overview of families and genera present in the Eurotiales and introduce an updated subgeneric, sectional and series classification for Aspergillus and Penicillium. Finally, a comprehensive list of accepted species in the Eurotiales is given. The classification of the Eurotiales at family and genus level is traditionally based on phenotypic characters, and this classification has since been challenged using sequence-based approaches. Here, we re-evaluated the relationships between families and genera of the Eurotiales using a nine-gene sequence dataset. Based on this analysis, the new family Penicillaginaceae is introduced and four known families are accepted: Aspergillaceae, Elaphomycetaceae, Thermoascaceae and Trichocomaceae. The Eurotiales includes 28 genera: 15 genera are accommodated in the Aspergillaceae (Aspergillago, Aspergillus, Evansstolkia, Hamigera, Leiothecium, Monascus, Penicilliopsis, Penicillium, Phialomyces, Pseudohamigera, Pseudopenicillium, Sclerocleista, Warcupiella, Xerochrysium and Xeromyces), eight in the Trichocomaceae (Acidotalaromyces, Ascospirella, Dendrosphaera, Rasamsonia, Sagenomella, Talaromyces, Thermomyces, Trichocoma), two in the Thermoascaceae (Paecilomyces, Thermoascus) and one in the Penicillaginaceae (Penicillago). The classification of the Elaphomycetaceae was not part of this study, but according to literature two genera are present in this family (Elaphomyces and Pseudotulostoma). The use of an infrageneric classification system has a long tradition in Aspergillus and Penicillium. Most recent taxonomic studies focused on the sectional level, resulting in a well-established sectional classification in these genera. In contrast, a series classification in Aspergillus and Penicillium is often outdated or lacking, but is still relevant, e.g., the allocation of a species to a series can be highly predictive in what functional characters the species might have and might be useful when using a phenotype-based identification. The majority of the series in Aspergillus and Penicillium are invalidly described and here we introduce a new series classification. Using a phylogenetic approach, often supported by phenotypic, physiologic and/or extrolite data, Aspergillus is subdivided in six subgenera, 27 sections (five new) and 75 series (73 new, one new combination), and Penicillium in two subgenera, 32 sections (seven new) and 89 series (57 new, six new combinations). Correct identification of species belonging to the Eurotiales is difficult, but crucial, as the species name is the linking pin to information. Lists of accepted species are a helpful aid for researchers to obtain a correct identification using the current taxonomic schemes. In the most recent list from 2014, 339 Aspergillus, 354 Penicillium and 88 Talaromyces species were accepted. These numbers increased significantly, and the current list includes 446 Aspergillus (32 % increase), 483 Penicillium (36 % increase) and 171 Talaromyces (94 % increase) species, showing the large diversity and high interest in these genera. We expanded this list with all genera and species belonging to the Eurotiales (except those belonging to Elaphomycetaceae). The list includes 1 187 species, distributed over 27 genera, and contains MycoBank numbers, collection numbers of type and ex-type cultures, subgenus, section and series classification data, information on the mode of reproduction, and GenBank accession numbers of ITS, beta-tubulin (BenA), calmodulin (CaM) and RNA polymerase II second largest subunit (RPB2) gene sequences.
Keywords: Infrageneric classification; ser. Implicati Houbraken & Frisvad; Pseudohamigera striata (Raper & Fennell) Houbraken, Frisvad & Samson; Acidotalaromyces lignorum (Stolk) Houbraken, Frisvad & Samson; Ascospirella lutea (Zukal) Houbraken, Frisvad & Samson; ser. Costaricensia Houbraken & Frisvad; ser. Raistrickiorum Houbraken & Frisvad; ser. Steyniorum Houbraken & Frisvad; ser. Fortuita Houbraken & Frisvad; ser. Teporium Houbraken & Frisvad; ser. Vitricolarum Houbraken & Frisvad; ser. Restricti Houbraken & Frisvad; Evansstolkia Houbraken, Frisvad & Samson; ser. Conjuncti Houbraken & Frisvad; Phialomyces arenicola (Chalab.) Houbraken, Frisvad & Samson; ser. Macrosclerotiorum Houbraken & Frisvad; ser. Hoeksiorum Houbraken & Frisvad; ser. Jiangxiensia Houbraken & Frisvad; Hamigera brevicompacta (H.Z. Kong) Houbraken, Frisvad & Samson; New sections; ser. Dalearum Houbraken & Frisvad; ser. Spinulosa Houbraken & Frisvad; ser. Kitamyces Houbraken & Frisvad; ser. Viridinutantes Houbraken & Frisvad; ser. Rolfsiorum Houbraken & Frisvad; ser. Estinogena Houbraken & Frisvad; ser. Nigri Houbraken & Frisvad; ser. Spathulati Houbraken & Frisvad; ser. Brevipedes Houbraken & Frisvad; ser. Sheariorum Houbraken & Frisvad; ser. Flavipedes Houbraken & Frisvad; ser. Circumdati Houbraken & Frisvad; ser. Calidousti Houbraken & Frisvad; ser. Samsoniorum Houbraken & Frisvad; ser. Bertholletiarum Houbraken & Frisvad; ser. Biplani Houbraken & Frisvad; ser. Japonici Houbraken & Frisvad; ser. Speluncei Houbraken & Frisvad; ser. Ambigui Houbraken & Frisvad; sect. Griseola Houbraken & Frisvad; Taxonomic novelties: New family; ser. Brevicompacta Houbraken & Frisvad; sect. Crypta Houbraken & Frisvad; ser. Copticolarum Houbraken & Frisvad; ser. Kiamaensia Houbraken & Frisvad; ser. Stellati Houbraken & Frisvad; Acidotalaromyces Houbraken, Frisvad & Samson; ser. Monodiorum Houbraken & Frisvad; ser. Ramigena Houbraken & Frisvad; in Aspergillus: sect. Bispori S.W. Peterson, Varga, Frisvad, Samson ex Houbraken; Penicillaginaceae Houbraken, Frisvad & Samson; ser. Canini Houbraken & Frisvad; ser. Coremiiformes Houbraken & Frisvad; ser. Nidulantes Houbraken & Frisvad; ser. Nodula Houbraken & Frisvad; ser. Robsamsonia Houbraken & Frisvad; in Aspergillus: ser. Acidohumorum Houbraken & Frisvad; sect. Lasseniorum Houbraken & Frisvad; ser. Crustacea (Pitt) Houbraken & Frisvad; ser. Kalimarum Houbraken & Frisvad; ser. Alliacei Houbraken & Frisvad; sect. Silvatici S.W. Peterson, Varga, Frisvad, Samson ex Houbraken; ser. Gracilenta Houbraken & Frisvad; sect. Formosana Houbraken & Frisvad; ser. Improvisa Houbraken & Frisvad; sect. Polypaecilum Houbraken & Frisvad; ser. Phoenicea Houbraken & Frisvad; ser. Penicillioides Houbraken & Frisvad; ser. Whitfieldiorum Houbraken & Frisvad; ser. Saturniformia Houbraken & Frisvad; ser. Multicolores Houbraken & Frisvad; Paecilomyces lagunculariae (C. Ram) Houbraken, Frisvad & Samson; Penicillago mirabilis (Beliakova & Milko) Houbraken, Frisvad & Samson; ser. Cervini Houbraken & Frisvad; ser. Corylophila Houbraken & Frisvad; ser. Erubescentia (Pitt) Houbraken & Frisvad; ser. Gallaica Houbraken & Frisvad; ser. Scabrosa Houbraken & Frisvad; ser. Simplicissima Houbraken & Frisvad; ser. Spelaei Houbraken & Frisvad; ser. Arxiorum Houbraken & Frisvad; ser. Salinarum Houbraken & Frisvad; ser. Brunneouniseriati Houbraken & Frisvad; ser. Nivei Houbraken & Frisvad; Penicillago moldavica (Milko & Beliakova) Houbraken, Frisvad & Samson; in Penicillium: ser. Alutacea (Pitt) Houbraken & Frisvad; ser. Sclerotiorum Houbraken & Frisvad; ser. Thermomutati Houbraken & Frisvad; ser. Pulvini Houbraken & Frisvad; ser. Georgiensia Houbraken & Frisvad; Pseudohamigera Houbraken, Frisvad & Samson; ser. Aurantiobrunnei Houbraken & Frisvad; ser. Heteromorphi Houbraken & Frisvad; ser. Idahoensia Houbraken & Frisvad; ser. Roseopurpurea Houbraken & Frisvad; ser. Unilaterales Houbraken & Frisvad; New combinations, species; New names; ser. Halophilici Houbraken & Frisvad; ser. Soppiorum Houbraken & Frisvad